(untitled) (Open Academia: Journal of Scholarly Research, 2024)
This article describes the importance of reflection in the development of professional pedagogical training of future teachers, the theoretical views of future teachers on self-confidence, increasing the need for pedagogical activity, the formation of creative motivation.